2021
DOI: 10.3390/app11041625
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aluminum Alloy–Silicon Carbide Functionally Graded Materials Developed by Centrifugal Casting Process

Abstract: The continuous development of modern industries rises the necessity for functionally graded materials. This research starts from the consideration that the incorporation of SiC particles in the molten aluminum alloy can be difficult due to the very low wettability of SiC particles. In order to increase their wettability, SiC particles were covered with a layer of metallic copper. The incorporation of SiC particles into the aluminum alloy mass was performed by centrifugal casting. The secondary hypoeutectic Al-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The SEM images obtained from the fracture zone of the stainless steel samples showed a predominantly brittle fracture, as can be seen in Figure 9 c,d, with more cracking zones and pores than the aluminum sample. Similar data were reported in [ 38 , 39 , 40 , 41 , 42 , 43 ]. In the case of the stainless steel samples, it was observed that the fracture angle between the applied traction load axis and the fracture surface was almost perpendicular and showed a relatively flat fracture surface, as seen in Figure 9 b.…”
Section: Resultssupporting
confidence: 90%
“…The SEM images obtained from the fracture zone of the stainless steel samples showed a predominantly brittle fracture, as can be seen in Figure 9 c,d, with more cracking zones and pores than the aluminum sample. Similar data were reported in [ 38 , 39 , 40 , 41 , 42 , 43 ]. In the case of the stainless steel samples, it was observed that the fracture angle between the applied traction load axis and the fracture surface was almost perpendicular and showed a relatively flat fracture surface, as seen in Figure 9 b.…”
Section: Resultssupporting
confidence: 90%
“…Silicon carbide (SiC) particles, a high-hardness ceramic material, were used as reinforcement as they can increase the hardness of the metallic matrix. Metal matrix composites with SiC particles incorporated in an aluminium matrix can be of interest in industries, such as aerospace, automotive, military, and sports [44]. For the study of dissimilar composites' production, SiC particles with a purity of 99.5% were used, although many other functional particles can be used depending on the desired functionality for the base material.…”
Section: Methodsmentioning
confidence: 99%
“…Centrifugal method can be used to produce bulk FGMs with a high control on composition and microstructure [62]. Samples of FGMs that include Al/SiC and Al/Al 3 Ti combinations have been successfully fabricated by centrifugal casting method [63].…”
Section: Conventional Manufacturing Of Fgmsmentioning
confidence: 99%